2007
DOI: 10.1186/1471-2180-7-115
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination by real-time PCR of four vaginal Lactobacillus species, Gardnerella vaginalis and Atopobium vaginae indicates an inverse relationship between L. gasseri and L. iners

Abstract: Background: Most studies of the vaginal microflora have been based on culture or on qualitative molecular techniques. Here we applied existing real-time PCR formats for Lactobacillus crispatus, L. gasseri and Gardnerella vaginalis and developed new formats for Atopobium vaginae, L. iners and L. jensenii to obtain a quantitative non culture-based determination of these species in 71 vaginal samples from 32 pregnant and 28 non-pregnant women aged between 18 and 45 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
109
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(136 citation statements)
references
References 52 publications
21
109
1
5
Order By: Relevance
“…A more recent study conducted in Kenya (Matu et al, 2009) found L. jensenii to be the most abundant species using culture and phenotypic identification methods. In Belgian women, L. iners is more dominant in altered vaginal microflora (De Backer et al, 2007). One group (Anukam et al, 2005;Anukam et al, 2006) did not however detect lactobacilli in BV cases whereas in the current study, of the nine Lactobacillus species detected, eight of them were present in the non-grade I samples.…”
Section: Discussioncontrasting
confidence: 52%
“…A more recent study conducted in Kenya (Matu et al, 2009) found L. jensenii to be the most abundant species using culture and phenotypic identification methods. In Belgian women, L. iners is more dominant in altered vaginal microflora (De Backer et al, 2007). One group (Anukam et al, 2005;Anukam et al, 2006) did not however detect lactobacilli in BV cases whereas in the current study, of the nine Lactobacillus species detected, eight of them were present in the non-grade I samples.…”
Section: Discussioncontrasting
confidence: 52%
“…These organisms are thought to play a role in resistance of the vaginal tract to colonization by pathogens, possibly through the production of lactic acid. L. iners is unusual among lactobacilli in that it may be detected during bacterial vaginosis (BV), a state in which G. vaginalis generally predominates and other Lactobacillus species are only rarely found at the vaginal mucosal surface (7,11,40,41). More recently, culture-independent studies of the vaginal microbiota have demonstrated that L. iners vaginal colonization may be considerably more prevalent than previously recognized, and in some cases it may be the most abundant organism detected (29,36).…”
mentioning
confidence: 87%
“…Furthermore, the relative proportions of community types differed among women of different ethnicities (1). The same four species have been reported to dominate the vaginal communities of healthy women across the world (2)(3)(4)(5)(6)(7)(8)(9). Even though the four Lactobacillus species commonly found and abundant in the human vagina have been isolated from other sites, their occurrence is extremely rare (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%